Ad

**log**^**2** 24 - **log**^**2** 3 = **log**^5 x Here something that would help you: **log** x base y = **log** x / **log** y **log** (x*y) = **log** x + **log** y **log** (x/y) = **log** x - **log** y so **log** 24 base **2** it's **log** 24 / **log** **2** etc. and if i get

Ad

...**log** (base **2**) 8? The answer should be 3....that is it is the inverse calculation of **2** cubed =8. Can any one help with the **log** calculation? Yes look you can't enter the base in calculators it's default ...

Ad

...**log** base **2** To calculate the **log** base **2** of a value, calculate its **log** and then divide by the **log** of **2**. You can use either the **log** or the ln keys, but be consistent. For example, to calculate the **log** ...

...**log**(**2**) from **log**(4) I get .301029957, the answer should be **2**, what is wrong? The answer for the problem **log**(4) - **log**(**2**) is actually 0.301, so the good news is that your calculator is working properly! ...

...**log** base **2** You can't. However, you can calculate the **log** base **2** of any number by calculating **log****2**(x) = **log**(x)/**log**(**2**) = ln(x)/ln(**2**) That is, the **log** base **2** of any number is the **log** of that number ...

**log**(x) / **log**(b) = ln(x) / ln(b) You can use either the common **log** (**log**) or the natural **log** (ln), as long as you're consistent. So, to calculate **log****2**(**2**.5), press **2** . 5 **log** / **2** **log** = or **2** . 5 ln / **2** ln

How can i perform **Log** 9 base **2** **log**(9)/**log**(**2**) (both base 10) is equal to **log**(9)base **2**. This works for anything, try it backwards and you'll find that **2**^(**log**(9)/**log**(**2**)) is equal to 9.

Question about FX-300MS Calculator

...**Log** Version = **2**,12,32,426 [HVD] OS Info 6 0 S **2** 0 [VC] ====== Start time: 1/5/2012, **2**:12:7 [VC] Module VC **Log** Version = 1,7,15,426 [VC] OS Info 6 0 S **2** 0 [VC] ====== Start time: 1/5/2012, **2**:12:7 [VC] ...

...**log**(x^**2**) + **log**(3/4) = **log**(2x + 3/4) **log**(3/4*x^**2**) = **log**(2x + 3/4) 3/4*x^**2** = 2x + 3/4 multiply equation by 4: 3x^**2** = 8x + 3 3x^**2** - 8x - 3 = 0 solve this quadratic eq. and you get x1 = 3 x2 = -1/3 does ...

Usually answered in minutes!

2,807 Questions

2,270 Questions

2,158 Questions

2,155 Questions

1,906 Questions